The Tree and the Myth of Creation in J.R.R. Tolkien - Varandas, Angélica (2017)
This chapter refers to the function of trees in Tolkien’s work, bearing in mind their role in Western myth, especially in Celtic and Scandinavian cultures as well as in Christian myth.